Endoscopic Posterior Cricoid Split and Rib Graft Without Tracheostomy: Case and Literature Review. (17th February 2021) - Jang, Minyoung; Grunstein, Eli
Abstract : Endoscopic posterior cricoid split and rib grafting (EPCS/RG) for the treatment of posterior laryngeal stenosis has some advantages over traditional open approaches, including improved surgical visualization and decreased morbidity. Many pediatric patients who undergo EPCS/RG have indwelling tracheostomy, which may be utilized to help manage the airway perioperatively. The role for de novo tracheostomy placement at the time of EPCS/RG is less clear. We present three cases from a tertiary children's hospital in which EPCS/RG was safely performed without tracheostomy. For patients with posterior laryngeal stenosis but without tracheostomy, EPCS/RG with endotracheal tube stenting might be a safe option. Laryngoscope, 131:E2599–E2602, 2021